Effect of local hyperthermia on respiratory indices of patients with chronic obstructive pulmonary disease - Masume Shahpasand; Ali Mohammadpour; Samane Najafi; Mansooreh Sobhani (Wolters Kluwer Medknow Publications, 2023)
Background: Change in respiratory indices is the most common problem in Chronic Obstructive Pulmonary Disease (COPD) patients. This problem is managed through pharmaceutical and non-pharmaceutical methods. This study aimed to determine local hyperthermia effect on respiratory parameters of COPD patients. Materials and Methods: This randomized controlled trial study was conducted on 46 patients with COPD referred to Allameh Bohlool Hospital in Gonabad, Iran in 2019. The participants were randomly assigned into two groups using quadrupled blocks. In both groups, a local pack was placed on the anterior chest for 23 min twice daily for 5 days. In the intervention group, the temperature of the hot pack was 50° and in the placebo group was the same as the body temperature. Respiratory indices including force vital capacity (FVC), forced expiratory volume in first second (FEV1), etc., were measured and compared before and after the last intervention in both groups. To gather data, demographic information form and respiratory indices record form were used. Results: Compared to before the intervention, all respiratory indices such as vital capacity (VC) (z = -4.25, p < 0.001), FEV1 (t22 = -114.18, p < 0.001), PEF (t22 = 5.91, p < 0.001) in the experimental group were increased significantly. Moreover, the difference in the mean respiratory indicators such as Pick Expiratory Flow rate (PEF) (t44 = 94.63, p < 0.001) and SPO2 (z = -3.27, p < 0.05) was also statistically significant in the two groups before and after the intervention. Conclusions: Local hyperthermia is effective in the improvement of respiratory indices among COPD patients, but it is recommended to conduct further studies before the implementation of this approach.